Write the expression below in expanded form.

2
3
·5
3
=

1 answer

To write the expression \( 2^3 \cdot 5^3 \) in expanded form, we will expand both terms separately.

  1. \( 2^3 = 2 \cdot 2 \cdot 2 \)
  2. \( 5^3 = 5 \cdot 5 \cdot 5 \)

Now, we can combine these expanded forms:

\[ 2^3 \cdot 5^3 = (2 \cdot 2 \cdot 2) \cdot (5 \cdot 5 \cdot 5) \]

In total, this gives us:

\[ 2 \cdot 2 \cdot 2 \cdot 5 \cdot 5 \cdot 5 \]

Therefore, the expression in expanded form is:

\[ 2 \cdot 2 \cdot 2 \cdot 5 \cdot 5 \cdot 5 \]